Relationship between HbA1c and capillary blood glucose self-monitoring in type 2 diabetics - Machado, Sara (2019)
Introduction. Diabetes Control and Complications Trial has established the importance of glycemic control in reducing the progression of retinopathy, nephropathy, and neuropathy in type 1 diabetics. There is little literature linking the frequency of glycemic monitoring with glycated hemoglobin A (HbA1c) in type 2 diabetics. The objectives were to assess the influence of glycemic self-monitoring on HbA1c in three groups of patients with type 2 diabetes (with insulin, with oral antidiabetics and with combination therapy). Methods. The glucometer capillary surveys of 117 patients were counted in the 30 days prior to the visit to the Integrated Diabetes Unit at Centro Hospitalar Tondela-Viseu. In the three groups considered, sociodemographic characteristics (age, gender, area of residence, household and schooling) were evaluated and compared. Results. There was no statistically significant association between HbA1c and the frequency of capillary glucose in any of the groups. In the evaluation of sociodemographic data, contrary to what was expected, the area of residence and schooling did not influence the value of HbA1c. Conclusion. These results question the role of glycemic monitoring in the metabolic control of type 2 diabetics, highlighting the need to implement therapeutic education programs so that these patients can adequately intervene in the therapeutic adjustment as a function of the information obtained by capillary glycemia.